The Role of Immunosuppressive Medications in the Pathogenesis of Hypertension and Efficacy and Safety of Antihypertensive Agents in Kidney Transplant Recipients - Divac, Nevena; NaumoviĦ#135, Radomir; StojanoviĦ#135, Radan; Prostran, Milica (Current Medicinal Chemistry, 2016)
The purpose of this review is to summarize current data on the role of immunosuppressants in the pathogenesis of hypertension and the efficacy and tolerability of major antihypertensive classes in kidney transplant recipients. Arterial hypertension is a common complication after kidney transplantation and a major risk factor for adverse outcome and graft rejection due to blood pressure elevation by immunosuppressive medications. Calcineurin inhibitors induce hypertension by a mechanism related to the imbalance of vasoactive substances endothelin and nitric oxide, and probably by causing overactivity of thiazide-sensitive sodium-chloride-cotransporter. Corticosteroids are well known for their hypertensive effects. The interactions of calcineurin inhibitors and mammalian target of rapamycin inhibitor sirolimus also promote hypertension. Management of arterial hypertension is a complex problem in the care of kidney transplant recipients. Target blood pressure values of <130/80 mm Hg are suggested by the National Kidney Foundation/ Kidney Disease Outcomes Quality Initiative. Calcium channel blockers may be useful in antagonizing the vasoconstrictive effects of calcineurin inhibitors. The renin-angiotensin system inhibitors seem a good option, especially in patients with proteinuria, however their effects on long-term graft and patient survival are controversial. β-Blockers could be beneficial in patients with coronary heart disease, but caution is required due to metabolic adverse effects. Thiazide diuretics could be the reasonable option for patients with glomerular filtration rate ≥30 mL/min/1.73 m2, also with caution regarding hypokalemia and glycemia. Until more evidence is provided, the choice of optimal antihypertensive therapy in kidney transplant recipients should be based on previous individual antihypertensive tolerability and efficacy, comorbidities, concomitant medications and post-transplant kidney function.
Keywords: β- blockers